INTERPRETASI BAWAH PERMUKAAN GUNUNG MERAPI DENGAN ANALISA GRADIENT DAN PEMODELAN 2D DATA GAYABERAT - Wisnu Agung Permadi; Agus Setyawan; Ilham Nurdien (Jurusan Fisika, Fakultas Sains dan Matematika, Universitas Diponegoro, 2016)
Gravity method research has been done in Merapi Volcano area. The data has been measured by BPPTKG Yogyakarta team with the number of point as much as 164 points. The aim of this research are to identify the subsurface structure and locate the position of Merapi Volcano magma chamber, so that a gradient analysis and 2D modelling based on Bouguer anomaly has been done. Gradient analysis apply first horizontal and second vertical gradient that is used to know the location and the type of structure on the research area. The result from this research show Bouguer anomaly with range value around -8.79 mGal to 305.46 mGal. The 2D modelling show Merapi volcano subsurface model that consist of 5 layers with the position of magma chamber is located in the third layer about 3300 m below the Merapi summit or 700 m below the mean sea level. Based on gradient analysis, there is a normal dipfault structure. This faults is indicated to be formed a basin on the Merapi summit toward westward leading directly to the Patuk Alap Alap Mountain and Kali Krasak.